The Family Context of Low-Income Parents Who Restrict Child Screen Time - Lampard, Amy; Jurkowski, J.; Davison, K. (Mary Ann Liebert, Inc. Publishers, 2013)
Background: The American Academy of Pediatrics recommends that parents restrict child screen time to two hours per day, but many preschool-aged children exceed this viewing recommendation. Modifying children’s viewing habits will require collaborating with parents, but little is known about the factors that influence parents’ capacity for effective screen-related parenting. This study aimed to identify the demographic, family and community contextual factors associated with low-income parents’ restriction of child screen time.Methods: Parents (N = 146) of children (age 2–5 years) attending Head Start centers in the United States completed a self-report survey in 2010 assessing parent and child screen use (television, DVD, video, video games, and leisure-time computer use), parent restriction of child screen time, and family (parent stress, social support, and life pressures) and community (neighborhood safety and social capital) factors.Results: Children were more likely to meet the American Academy of Pediatrics screen time recommendation if their parent reported high restriction of child screen time. Parent and child demographic characteristics were not associated with parents’ restriction of child screen time. In multivariate analysis, less parent screen time, fewer parent life pressures, and greater socialsupport were associated with parents’ high restriction of screen time.Conclusion: Family contextual factors may play an important role in enabling low-income parents to restrict their children’s screen time. When counseling low-income parents about the importance of restricting child screen time, practitioners should be sensitive to family contextual factors that may influence parents’ capacity to implement this behavior change.